Socioeconomic Determinants of Nutritional Status of Children in Lao PDR: Effects of Household and Community Factors - Kamiya, Yusuke (Journal of Health, Population and Nutrition, 2011)
The prevalence of undernutrition among Lao children is among the highest in the region. However, the determinants of childhood undernutrition in Laos have not been fully analyzed. This paper, using the dataset of the Lao Multiple Indicator Cluster Survey 3, which is a nationally-representative sample in Laos, investigated the effects of socioeconomic factors at both household and community levels on the nutritional status of children. In the estimation, a multilevel linear model with random-intercepts was used for estimating the determinants of child anthropometric indices. The empirical results revealed that children from households in southern Laos and from ethnic minority groups were less-nourished. Level of education of parents, attitudes of mothers towards domestic violence, assets of household, local health services, and the condition of sanitation and water were considered to be important determinants of nutritional status of children. The pattern of growth-faltering in children by age was identified. Children aged 12-59 months were less-nourished than those aged 0-11 months. The empirical results were consistent with the collective household model which incorporates a decision-making process within the household. Since there is scarce evidence about the predictors of childhood undernutrition in Laos, the findings of this study will serve as a benchmark for future research. Key words: Anthropometry; Child health; Child nutrition disorders; Child nutritional status; Infant health; Infant nutrition disorders; Infant nutritional status; Socioeconomic factors; Laos DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8449 JHPN 2011; 29(4): 339-348